Reclaiming public health services in Uganda - Nabwowe Kasule, Angella; Mncwabe, Nokukhanya (Economic and Social Rights Advocacy (ESRA), 2021)
The Covid-19 pandemic has reinforced the importance of strong public health services to deliver equitable healthcare. The countries that most successfully navigated the pandemic tended, overwhelmingly, to have entrenched and resilient public health systems. The clarion call for “health for all” – regardless of ability to pay - is thus unsurprising. The global pandemic has seriously underscored the need for strong public health systems and strong government stewardship of healthcare-related infrastructure, human resources and financing. Calls to address this need were prevalent at the 73rd World Health Assembly, which was characterized by heated debates on healthcare access and health as a global public good, which were particularly animated during the drafting of a Covid-19 resolution. Discussions centred on a just, post Covid-19 economic recovery also reignited public debate about the chronic underfinancing of public health; with increasing pressure exerted on governments to “build back better,” by, among other things, reclaiming public services to make them not only the first, but more importantly, the most responsive health system, especially for poor and vulnerable persons.